Content analysis of the book My Beautiful Language for the sixth grade of primary school in light of constructive thinking skills in public schools in The Kingdom of Saudi Arabia - Al-Tarisi, Hessa Jahz Zaben; Abdul Khaliq, Abdullah (Journal of Curriculum and Teaching Methodology, 2025)
The study aimed to analyze the content of the “My Beautiful Language” textbook for the sixth grade in light of constructive thinking skills. To achieve the study's objective, the researcher employed the descriptive-analytical method. The study population consisted of all “My Beautiful Language” textbooks for the primary school level, while the study sample was limited to the sixth-grade textbook. To answer the study questions, the researcher developed a content analysis tool for the “My Beautiful Language” textbook in light of constructive thinking skills. After verifying the validity and reliability of the tool, it was applied to the study sample. Percentages and frequencies were used to answer the research questions. The results of the study showed that constructive thinking skills are present in the “My Beautiful Language” textbook for the sixth grade, but at varying levels across the six units. In the first part, planning skills were the most prevalent at 53.61%, followed by monitoring and control skills at 28.92%, and evaluation skills at 17.47%. In the second part, evaluation skills were the most prevalent at 66.15%, followed by monitoring and control skills at 20.31%, and planning skills at 13.54%. When analyzing the textbook as a whole (both parts), evaluation skills were the most included at 43.58%, followed by planning skills at 32.12%, and finally monitoring and control skills at 24.30%. These findings highlight the need for a more balanced distribution of constructive thinking skills across both parts of the textbook.Based on the findings of the study, the researcher recommended increasing the inclusion of constructive thinking skills in the “My Beautiful Language” textbook for the sixth grade, ensuring a balance among all skills so that no single skill overshadows the others. This would allow constructive thinking skills to become a foundational framework integrated throughout the curriculum.
Keywords: Constructive Thinking Skills; Content Analysis; My Beautiful Language Textbook; Sixth Grade; The Kingdom of Saudi Arabia